The impact of a training program on developing focus attention among football seniors players ( field study of chaouia footabll club) - Djouani , mahdi; heriet, mohamed elhacen elmaamoune; haddi, ali (sports creativity, 2025)
The current research aims to identify the impact of an individual training program on focusing the attention of football players and to identify the differences between the players in attention focus, the researcher used the two-group experimental method (control and experimental), and the search sample included 20 players from the uschaouia Club. The researcher conducted the pre-test using the attention methods test in the group games of Dr. Mohammad Hassan Alawi, after which the 18-module training program was implemented. After completing the program application, the researcher performed the post-tests where the applied program had a positive effect on developing the focus of attention in the sample study and the researcher recommended that the psychological aspect should be taken into consideration, especially the focus of attention related to various football skills